2020
DOI: 10.1093/gigascience/giz157
|View full text |Cite
|
Sign up to set email alerts
|

Genome and population sequencing of a chromosome-level genome assembly of the Chinese tapertail anchovy (Coilia nasus) provides novel insights into migratory adaptation

Abstract: Background Seasonal migration is one of the most spectacular events in nature; however, the molecular mechanisms related to this phenomenon have not been investigated in detail. The Chinese tapertail, or Japanese grenadier anchovy, Coilia nasus, is a valuable migratory fish of high economic importance and special migratory dimorphism (with certain individuals as non-migratory residents). Results In this study, an 870.0-Mb hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…Our results also showed that the presence of lineage A (freshwater individuals) occupied low frequencies of haplotypes in the low reaches of the Yangtze implied extremely limited gene flow existed between the anadromous group and freshwater group. Our result was also supported by the phylogenetic analysis of representative individuals clearly corresponding to the anadromous group and freshwater group of C. nasus based on the entire genome SNP set (Xu et al, 2020). The middle reaches of the Yangtze River harbors a large number of lakes with different sizes (e.g., Tianezhou, Poyang Lake, and Dongting Lake), which would support optimum living and spawning conditions (e.g., fresh water, water temperature (15∼27.5 • C), depth (0.5∼3.0 m), suitable current (0.057∼0.075 m/s), and abundant zooplankton required for spawning) for freshwater group of C. nasus.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our results also showed that the presence of lineage A (freshwater individuals) occupied low frequencies of haplotypes in the low reaches of the Yangtze implied extremely limited gene flow existed between the anadromous group and freshwater group. Our result was also supported by the phylogenetic analysis of representative individuals clearly corresponding to the anadromous group and freshwater group of C. nasus based on the entire genome SNP set (Xu et al, 2020). The middle reaches of the Yangtze River harbors a large number of lakes with different sizes (e.g., Tianezhou, Poyang Lake, and Dongting Lake), which would support optimum living and spawning conditions (e.g., fresh water, water temperature (15∼27.5 • C), depth (0.5∼3.0 m), suitable current (0.057∼0.075 m/s), and abundant zooplankton required for spawning) for freshwater group of C. nasus.…”
Section: Discussionsupporting
confidence: 76%
“…The middle reaches of the Yangtze River harbors a large number of lakes with different sizes (e.g., Tianezhou, Poyang Lake, and Dongting Lake), which would support optimum living and spawning conditions (e.g., fresh water, water temperature (15∼27.5 • C), depth (0.5∼3.0 m), suitable current (0.057∼0.075 m/s), and abundant zooplankton required for spawning) for freshwater group of C. nasus. The optimum living and spawning conditions for freshwater group of C. nasus, especially high quality fresh water, gentle currents and abundant zooplankton, could not be found in the low reaches of the Yangtze River and the China coast (Xu et al, 2020). The effect of isolation (the middle reaches of the Yangtze River vs. the low reaches of the Yangtze River and the China coast) and adaptation to the new freshwater habitats of the middle reaches of the Yangtze River for C. nasus freshwater form might be responsible for the module of finitely asymmetric gene flow from freshwater to anadromous populations (Zhang, 2001;Schluter and Conte, 2009).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The published chromosome-level genome assembly for C. nasus ( Xu et al. 2020 ) contains a total of 81,894 Eco RI restriction sites (one per 10 kb) across 24 linkage groups (chromosomes).…”
Section: Resultsmentioning
confidence: 99%